Decision support system development for integrated management of European coastal lagoons. (February 2015) - Casini, Marco; Mocenni, Chiara; Paoletti, Simone; Pranzo, Marco
Abstract: In this paper, a general framework for the development of Decision Support Systems (DSSs) for the management of coastal lagoons is presented. The proposed DSS structure integrates the information provided by several models accounting for different characteristics of lagoon ecosystems, including biogeochemical, hydrodynamic, ecological and socio-economic aspects. Outputs and indicators provided by the models are used to accomplish the decision task by the application of multicriteria analysis. Model uncertainty and robustness with respect to uncontrollable factors are addressed. Application of the proposed DSS structure to five lagoons located in the Mediterranean area is discussed, with special focus on the management of clam farming in the Sacca di Goro lagoon (Italy). Thanks to its flexibility, the proposed DSS structure is also applicable in decision problems arising in different fields. Highlights: A general model-based DSS for the management of coastal lagoons is presented. Complex biological, chemical and socio-economic processes are considered. The application to the management of clam farming in the Sacca di Goro is described.